Fish Diversity at Pancheshwar Multipurpose Project Area in Mahakali River - Saund, Tej B; Thapa, Jham B; Bhatt, Harish P (Nepal Journal of Science and Technology, 2013)
A study was carried out to prepare a baseline information on water quality and freshwater fish diversity at Pancheshwar Multipurpose Project area in Mahakali river. The study was conducted in autumn (October 2008) and summer (June 2009). A total of 24 fish species belonging to 3 orders, 4 families and 13 genera were recorded during the investigation period. Cypriniformes was the most dominant order accounting 75% of total fish species. Siluriformes and Synbranchiformes accounted for 21% and 4% of fish species composition respectively. Spawning and rearing areas in study sites were evenly distributed providing a suitable habitat for both cold and warm water fish species. The water quality parameters, i.e., water temperature (20.50-22.63 0C), DO (8.58-11.85 mg/l) and pH (6.93-7.20) were found within the suitable range supporting diverse fish species. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 225-230 DOI: http://dx.doi.org/10.3126/njst.v13i2.7741